2010
DOI: 10.1021/ac1014518
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Detection of Model Bioaerosol Particles

Abstract: A new technique for the detection of bioaerosols is presented, utilizing particle combustion/ionization in a premixed hydrogen/oxygen/nitrogen flame plasma, followed by gas phase electrochemical detection. Bermuda grass pollen (Cynodon dactylon, one of the most common causes of pollen allergy) and black walnut pollen (Juglans nigra) were used as model bioaerosol particles. We demonstrate that single particle detection can be comfortably achieved by zero current potential measurements between two platinum elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Lee et al, 2008;Seshadri et al, 2009;Yoon et al, 2010). Electrochemical, immunochemical and immune biological methods have also been investigated for ambient PBAP characterisation (Rishpon et al, 1992;Spurny, 1994;Sarantaridis and Caruana, 2010;Schmidt and Bauer, 2010). It should be noted here that complementary instruments such as biological aerosol particle concentrators have also helped enable analyses by a variety of instruments (e.g.…”
Section: Miscellaneous Non-optical-methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, 2008;Seshadri et al, 2009;Yoon et al, 2010). Electrochemical, immunochemical and immune biological methods have also been investigated for ambient PBAP characterisation (Rishpon et al, 1992;Spurny, 1994;Sarantaridis and Caruana, 2010;Schmidt and Bauer, 2010). It should be noted here that complementary instruments such as biological aerosol particle concentrators have also helped enable analyses by a variety of instruments (e.g.…”
Section: Miscellaneous Non-optical-methodsmentioning
confidence: 99%
“…Laserinduced breakdown spectroscopy (LIBS) has easily been the most common form of BS method and has been employed to characterise pollen (Boyain-Goitia et al, 2003), and fungal spores (Hybl et al, 2003), bacteria (Morel et al, 2003) and a variety of biological aerosol particle types (Samuels et al, 2003). Other forms of elemental analysis such as spark-induced breakdown spectroscopy (SIBS), particle-induced X-ray emission (PIXE) and various forms of combustion analysis have also been utilised for laboratory study of biological aerosol (Sarantaridis and Caruana, 2010;Schmidt and Bauer, 2010).…”
Section: Light Detection and Ranging (Lidar) And Remote Sensingmentioning
confidence: 99%
“…The physical origin of this potential difference was discussed at length in ref. 26. In that work we recognised that the potential is mainly due to a diffusion potential established between the indicator and ground electrode.…”
Section: Physical Origin Of Potential Differencementioning
confidence: 97%
“…More details of the setup can be found in ref. 26. For this study 6 different flame compositions were used as shown in pollen due to its easier aerosolisation at our lab conditions.…”
Section: Experimental Burner Systemmentioning
confidence: 99%
See 1 more Smart Citation